A130 SAFETY OF COMBINATION BIOLOGIC AND ANTI-REJECTION THERAPY POST-LIVER TRANSPLANTATION IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: LONDON ONTARIO EXPERIENCE. (15th March 2019) - Al Draiweesh, S; Ma, C; Alkhattabi, M; McDonald, C; Chande, N; Feagan, B G; Gregor, J C; Khanna, R; Marotta, P; Sandhu, A S; Qumosani, K; Teriaky, A; et al.
Abstract: Background: Despite anti-rejection immunosuppressive therapies post-liver transplantation (LT), patients with concurrent inflammatory bowel disease (IBD) may have persistent bowel inflammation that requires addition of biologic therapy. Aims: To evaluate the safety of combination biologic and anti-rejection therapy in IBD patients after LT. Methods: The LT Registry at London Health Sciences Centre (LHSC) was searched to identify all patients undergoing LT from 1985–2018. IBD patients initiated on biologic treatment post-LT, in addition to anti-rejection therapy, were eligible for inclusion. Medical chart review was conducted to extract safety outcomes, including rates of infections, malignancy, colectomy and death. Results: 19 patients were included (78.9% male, mean age 46.0 years, 8 patients with ulcerative colitis), followed for a median duration of 19 months (IQR 5.8, 30.8). Indications for LT included: primary sclerosing cholangitis (PSC) (14/19, 73.7%), autoimmune hepatitis (AIH) (2/19, 10.5%), AIH-PSC overlap syndrome (2/19, 10.5%), and biliary atresia (1/19, 5.3%). Post-LT, six patients were treated with only TNF antagonists (infliximab in 5 patients, golimumab in 1 patient); eight patients with only anti-integrin therapies (vedolizumab in 7 patients, natalizumab in 1 patient); and five patients with sequential TNF antagonists followed by either ustekinumab (n=2) or vedolizumab (n=3). Six patients required long-term prednisone. The most commonly used anti-rejection therapies were tacrolimus and mycophenolate mofetil. Disease course was complicated by infections in nine patients (47.4%), most commonly Clostridium difficile colitis (4/19, 31.6%). One patient had recurrent C. difficile infection and one patient had CMV colitis and viremia. Other infections included cholangitis (n=2), perianal abscess (n=1), JC virus seroconversion but without progressive multifocal leukoencephalopathy (n=1) and hospital-acquired pneumonia (n=1). Two patients required colectomy for refractory colitis. One patient required re-transplantation due to PSC recurrence. No deaths or malignancies were reported although one patient developed low grade colonic dysplasia. Conclusions: This is the largest reported case series from a single center to date evaluating the safety of combination biologic therapy with anti-rejection regimens in IBD patients post-LT. Whilst there appeared to be an increased risk of enteric infections, especially Clostridium difficile, there were no life-threatening infections reported. Active screening for enteric infections should be pursued in these patients presenting with increased IBD symptoms. Funding Agencies: None